(untitled) (Revista Iberoamericana de Bioética, 2024)
In March 2020, faced with the spread of the COVID-19 pandemic, Spain imposed one of the strictest lockdowns in the Western world. As an extreme public health intervention, a lockdown poses a profound ethical conflict. At a political level, this conflict becomes a conflict of fundamental rights and, ultimately, human rights. This paper presents an overview of the affected rights, and discusses the lockdown imposed by Spain and subsequently copied by Latin American countries through the prism of the ethics involved in responding to and controlling epidemics. Lockdown was an unprecedented intervention, its effectiveness unknown; it entailed a serious violation of civil rights, with no scientific base and no real epidemiological outcomes. Avoiding the same mistake in future pandemics depends partly on scrupulous respect for the ethical principles that are already established in applicable law.